Estudo comparativo da citotoxicidade e alterações citopatológicas induzidas pela microcistina-LR em linhas celulares renais e hepáticas (Vero e HepG2). - Menezes, Carina (2012)
Microcystin-LR (MCLR) is a potent hepatotoxin produced by freshwater cyanobacteria, being responsible for acute and chronic hazards to animal and human health. Despite the increasing recognition of its toxic effects, the cellular basis of MCLR-induced toxicity is still poorly understood. In this work, morphological, ultrastructural and biochemical (MTT and Neutral Red-NR) analyses were performed to evaluate the effects of a semi-purified MCLR-containing cyanobacterial extract on Vero and HepG2 cell lines. Our results showed that cell viability decayed markedly after 24h of exposure to toxin concentrations greater than 25μg.ml-1 in both cell lines. The ultrastructural analysis revealed that at subcytotoxic MCLR doses, cells presented large cytoplasmic vacuoles, which were more prominent in HepG2. These vacuoles showed to be enriched in the LC3 protein, suggesting that autophagy is an early cellular response to MCLR. At higher doses, the specific staining Acridine Orange (AO) and Rhodamine-123 (Rh-123), demonstrated that lysosome destabilization precedes mitochondrial dysfunction. Besides, MCLR seemed to induce a decrease in the expression of the anti-apoptotic endoplasmic reticulum protein Grp94, particularly evident in HepG2 cells. These results suggest that MCLR-induced cytotoxicity involves a considerable crosstalk among several organelles and that despite some cell-specific features, the general cellular basis underlying this toxicity is common to both Vero and HepG2 cells.